Zambian Invertebrate Scoring System (ZISS): A macroinvertebrate-based biotic index for rapid bioassessment of southern tropical African river systems. Issue 4 (30th November 2018) - Dallas, HF; Lowe, S; Kennedy, MP; Saili, K; Murphy, KJ
Abstract : An extensive survey of tropical rivers, conducted during 2009–2012 throughout Zambia, collected 151 samples of benthic macroinvertebrates, located on 95 rivers in six of the nine freshwater ecoregions. Associated data for physico-chemistry, human activities and ecosystem stressors were collected. Data were used to develop and test a new Rapid Bioassessment Protocol (the Zambian Invertebrate Scoring System: ZISS) for assessment of water quality and river condition in both wadeable and non-wadeable rivers. ZISS, which is based on the South African Scoring System (SASS), includes a total of 85 taxa, of which 79 are shared with SASS. Assignment of sensitivity weightings to new ZISS taxa was based on sensitivity weightings of closely related SASS families; known life-history modes and anatomical adaptations; and correlation of occurrence to impact ratings. The ability of the ZISS to measure impacts was assessed by determining the relationships between ZISS metrics and impacts. ZISS data for the Kafue River demonstrated the efficacy of the ZISS for detecting moderate to high impacts on water quality and river condition. ZISS represents a major step in developing a user-friendly, widely applicable, macroinvertebrate-based biotic index, which can provide easily interpretable assessments of river condition for southern tropical African rivers.